2010
DOI: 10.1111/j.1469-185x.2009.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

How do plants “notice” attack by herbivorous arthropods?

Abstract: Precise and deep comprehension of plant responses to herbivorous arthropods requires detailed knowledge of how a plant "notices" the attack. Herbivore attack is not restricted to plant wounding by feeding, but instead different phases of attack that elicit a plant response need to be distinguished: touch, oviposition and feeding. Touch, secretions released with eggs and regurgitate delivered during feeding may act in concert as elicitors of plant defence. Here, we discuss the current knowledge of what a plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
142
0
3

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(148 citation statements)
references
References 166 publications
3
142
0
3
Order By: Relevance
“…In addition to their feeding pattern, compounds in the saliva or regurgitant of herbivores have a major effect on the interactions with the plant (19,30). Plants may distinguish the type of attacking herbivore by the perception of herbivore-associated elicitors (3,19,32), but herbivores may also suppress plant responses by elicitors in their saliva (33,34). The elicitors in saliva are often species-specific and diverse in structure (35,36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to their feeding pattern, compounds in the saliva or regurgitant of herbivores have a major effect on the interactions with the plant (19,30). Plants may distinguish the type of attacking herbivore by the perception of herbivore-associated elicitors (3,19,32), but herbivores may also suppress plant responses by elicitors in their saliva (33,34). The elicitors in saliva are often species-specific and diverse in structure (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Such interactions between plants and carnivorous arthropods may ultimately increase fitness of the plants (1)(2)(3). Plant traits involved in such interactions include those that provide a predator/parasitoid with a resource such as, for example, food or shelter, or with information on the presence and abundance of herbivorous prey/hosts (4,5).…”
mentioning
confidence: 99%
“…On the other hand, herbivores have developed intricate strategies to suppress plant defensive responses (Musser et al 2002), and it has been proposed that they may do so already during oviposition in order to give to offspring an optimal start upon emergence (Hilker and Meiners 2010). Following this idea, it has recently been demonstrated that the application of crushed Pieris brassicae L. (Lepidoptera: Pieridae) eggs to Arabidopsis thaliana (L.) activates SAdependent defenses, which function against pathogens, but enhances larval growth of Spodoptera littoralis Boisd.…”
Section: Introductionmentioning
confidence: 99%
“…Yumurtadan çıkan yavru bireylerin beslenmesi ve gelişerek yeni nesil verebilmeleri için ergin dişi bireyler, yumurta bırakacakları yeri özenle ararlar ve yumurtalarını en güvenli gördükleri yere bırakırlar (Pehlivan, 1981). Dişi birey yumurtalarını bitki üzerine bıraktıktan sonra, bitkiler bırakılan yumurtalara karşı doğrudan veya dolaylı olarak tepki gösterme eğiliminde bulunurlar (Hilker & Meiners, 2010). Bu durum öncelikle bitkinin morfolojisinden kaynaklanan tepki olarak ortaya çıkmaktadır.…”
Section: Konukçu Bitkinin Böcek Yumurtası üZerine Etkisiunclassified